Genghis Khan and the Mongol war machine - Peers, Chris (Pen & Sword Military, 2015)
As a soldier and general, statesman and empire-builder, Genghis Khan is an almost legendary figure. His remarkable achievements and his ruthless methods have given rise to a sinister reputation. As Chris Peers shows, in this concise and authoritative study, he possessed exceptional gifts as a leader and manager of men - he ranks among the greatest military commanders - but he can only be properly understood in terms of the Mongol society and traditions he was born into. His book offers a fascinating fresh perspective on Genghis Khan the man and on the armies he led.